Hanes Cymry - Lleiafrifoedd Ethnig yn y Gwareiddiad Cymraeg [A History of the Welsh - Ethnic Minorities in Welsh-language Civilization) - Simon Brooks (Gwasg Prifysgol Cymru / University of Wales Press, 2020)
Ceir yma hanes cyflawn amrywiaeth ethnig yn y diwylliant Cymraeg ei iaith. Mae'r llyfr hefyd yn mynd i'r afael a gwahaniaeth ieithyddol yng nghyswllt trafodaethau cyfredol am ethnigrwydd, gan ddadlau o blaid modelau a theori ynghylch amrywiaeth ethnig oddi mewn i gymunedau ieithyddol lleiafrifol nad ydynt o raid yn seiliedig ar wybodaeth Angloffon. / A full history of ethnic diversity in the Welsh-language community. The book also discusses linguistic difference in the context of contemporary debate around ethnicity, arguing in favour of various models and theories about ethnic diversity within minority language communities that are not in every case based upon Anglophone knowledge.